Genetic diversity and population structure of the Pampas Fox, Lycalopex gymnocercus, In a Human-Dominated Landscape of Southern Espinal, Argentina - Pizzano, Brenda (2021)
Habitat fragmentation and the associated landscape connectivity loss can reduce gene flow among populations, which could lead to a decrease in genetic variability, and an increase in the extinction risk of a species. The main goal of this study was to provide genetic diversity and population structure data for Pampas foxes from the southern Argentine Espinal ecoregion. Through the analyses of 30 tissue samples collected during 2013-2018, we were able to genotype 23 individuals at 18 microsatellite loci. Results indicate high diversity values, and exhibiting an average of 10 alleles per locus (min= 6, max= 13), 0.71 (range= 0.35-0.91) of mean observed heterozygosity and 0.83 (min= 0.61, max= 0.91) of mean expected heterozygosity. Bayesian analyses suggest no population structure. Finally, we did not detect a pattern of isolation by distance. The high habitat adaptability and the generalist feeding behavior of Pampas fox may explain our findings, which are in agreement with the general patterns described for other fox species. The panel of microsatellites employed in this study proved to be suitable for Pampas fox genotyping and it can be used in further genetic assessments needed to validate and expand our understanding of its population genetics.